2005
DOI: 10.1029/2004gl021388
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of underthrust sediments at the Costa Rican subduction zone: Scale dependence and implications for dewatering

Abstract: [1] Sediment permeability is a key parameter controlling overpressure development and fluid egress at subduction zones. Existing data compilations for argillaceous sediments illustrate that scale effects on permeability are generally minor, although this is a topic of active debate. Here, we report laboratory permeability measurements from sediments incoming to the Costa Rican subduction zone, at porosities from 26% to 78%. We then apply a method for directly estimating average permeability at the scale of sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…Our results for Nankai are slightly higher than those at N. Barbados and considerably lower than at Costa Rica. This is consistent with low permeability expected for the clay rich underthrust section at N. Barbados, and with the fact that initial burial to ∼400 mbsf at Nankai prior to underthrusting results in lower overall porosity (and thus lower permeability) than at nonaccretionary margins like Costa Rica where the entire section is underthrust [e.g., Saffer , 2003; Saffer and McKiernan , 2005; Screaton , 2006]. …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our results for Nankai are slightly higher than those at N. Barbados and considerably lower than at Costa Rica. This is consistent with low permeability expected for the clay rich underthrust section at N. Barbados, and with the fact that initial burial to ∼400 mbsf at Nankai prior to underthrusting results in lower overall porosity (and thus lower permeability) than at nonaccretionary margins like Costa Rica where the entire section is underthrust [e.g., Saffer , 2003; Saffer and McKiernan , 2005; Screaton , 2006]. …”
Section: Discussionsupporting
confidence: 76%
“…Past studies have indicated that at many subduction zones dewatering of the underthrusting layer is primarily vertical, especially as distance from the trench increases. Thus, a one‐dimensional model is sufficient to simulate the process of interest [ von Huene and Lee , 1982; Screaton and Saffer , 2005; Saffer and McKiernan , 2005; Gamage and Screaton , 2006]. The governing equation for one‐dimensional, transient fluid flow is [ Bear , 1972; Neuzil , 1995] where h is hydraulic head (m), t is time (s), K is hydraulic conductivity (m s −1 ), S S is specific storage (m −1 ), and Γ is a source term representing loading processes (and in a subset of our simulations, mineral dehydration) (m s −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of our analysis, the Piezoprobe will achieve 90% dissipation 14 times sooner than the DVTPP (Figure 16). Coefficients of consolidation for sediments penetrated in the Ocean Drilling Program range from 4 × 10 −8 to 2 × 10 −6 m 2 /s (Table 5) [ Dugan and Flemings , 2003; Saffer and McKiernan , 2005; Tan , 2004]. For this range of properties it will take from 6 min to 5 hours to achieve 90% dissipation with the Piezoprobe.…”
Section: Discussionmentioning
confidence: 99%
“…In situ permeability measurements have been conducted in a small number of boreholes using drill stem packer systems [e.g., Screaton et al ., ; Fisher & Zwart , ; Becker & Davis , ]. More commonly, in situ permeability is extrapolated from laboratory measurements on core samples [e.g., Saffer & McKiernan , ; Reece et al ., ; Boutt et al ., ], estimated from the pore pressure response to tidal or other transient forcing measured in instrumented boreholes [e.g., Wang & Davis , ] or inferred from inverse modeling [e.g., Bekins et al ., ; Saffer & Bekins , ; Spinelli et al ., ].…”
Section: Introductionmentioning
confidence: 99%